Optimisation of a flow cytometry antibody panel to detect BCG-induced innate responses in infants - Mwambene, Temwa Dango (Department of Pathology, 2024)
The outcome of exposure to Mycobacterium tuberculosis is highly variable ranging from clearance, latency to a wide spectrum of subclinical and clinical tuberculosis (TB) disease. The underlying basis of the variable disease outcomes to mycobacterial exposure is largely unknown and is thought to involve a complex interplay between genetic variation in both host and pathogen. This is further convoluted by factors such as age, geography, coinfections including human immunodeficiency virus (HIV) and previous Bacillus Calmette–Guérin (BCG) vaccination. As it stands, other than inborn errors in key mycobacterial susceptibility genes both animal and human studies have not found many genetic polymorphisms that are strongly and reproducibly associated with increased mycobacterial disease susceptibility and/or BCG vaccine efficacy. Given the complexity of the interplay between the variability in disease susceptibility, BCG vaccine efficacy and human exposure to genetically diverse pathogens there is a need to study both host and pathogen genetic factors that contribute to increased TB disease susceptibility. This will facilitate rational design of more broadly efficacious interventions. This MSc project is nested in a project which aims to uncover the genetic factors that result in variable responses to BCG vaccination and in so doing, expand the basis of learning for novel TB vaccine candidates. The overall aim of this MSc was to optimise a flow cytometry panel to measure the BCG-induced innate immune responses in infants. The innate response to BCG was characterised by whole blood intracellular cytokine staining of banked, previously stimulated immune cells from 25, 10-week-old, HIV-uninfected, infants. The cohort is a subset of participants of a randomised control trial conducted in Worcester, South Africa. A 13-colour flow cytometry antibody panel was successfully optimised for enumerating and measuring cytokine and cell maturation marker expression by neutrophils, monocytes, pDCs, mDCs and T cells in response to BCG stimulation. Expression of cytokines (IFNg, IL-6, TNF) and maturation markers (CD40, PD-L1) by these cell subsets to BCG stimulation were quantified, allowing identification of single nucleotide polymorphisms that associate with variability in innate responses to BCG. Results from this MSc thus inform the bigger project which aims to determine genetic determinants of innate responses to BCG and TB disease risk.